2014
DOI: 10.1007/s11095-014-1392-5
|View full text |Cite
|
Sign up to set email alerts
|

New strategy to surface functionalization of polymeric nanoparticles: one-pot synthesis of scFv anti-LDL(−)-functionalized nanocapsules

Abstract: The one pot synthesis, using the ligand-metal-chitosan-lecithin complex to functionalize the surface of the biodegradable nanocapsules, maintained the active site of the antibody fragment making the device interesting for applications in nanomedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…This means that each nanoparticle in the suspension can carry about 1200 molecules of Mel bringing a large load of Mel to the target. In addition, LNC per se showed antioxidant properties [46]; LNC decreased ascorbyl radical formation, reducing in vitro lipid peroxidation of liposomes.…”
Section: Discussionmentioning
confidence: 95%
“…This means that each nanoparticle in the suspension can carry about 1200 molecules of Mel bringing a large load of Mel to the target. In addition, LNC per se showed antioxidant properties [46]; LNC decreased ascorbyl radical formation, reducing in vitro lipid peroxidation of liposomes.…”
Section: Discussionmentioning
confidence: 95%
“…[61][62][63] It is beyond question that involvement of reactive oxygen species (ROS) and RNS affects melanoma induction and development, but the complexity of actions has generated conflicting data. [64][65][66] Therefore, we will make efforts to characterize the mechanisms of LNC on ROS and RNS systems and to establish the real role of ROS/RNS balance and its involvement in the toxicity of LNC on melanoma cells.…”
Section: Drewes Et Almentioning
confidence: 99%
“…Indeed, recent studies have shown the biological activity of drug-free nanoparticles. The first reported the antioxidant effects of LNC in a lipid peroxidation model, 63 and the other showed the action of drug-free chitosancoated poly(iso-butyl cyanoacrylate) nanoparticles against Trichomonas vaginalis. 75 Hence, results herein highlight that the molecular interactions between the constituents of LNC affect the supramolecular structure as well as its physicochemical characteristics.…”
mentioning
confidence: 99%
“…In the active targeting, the nanoparticle is selectively recognized by receptors on the surface of cells. Since ligand-receptor interactions can be highly selective, which would allow for a more precise targeting of a specific site in the body [76,77,90,[93][94][95][96]. The approaches using active vectorization with nanoparticles are a quite challenging, and are currently one of the main goals of several studies in nanotechnology.…”
Section: Active and Passive Targeting Of Nanoparticlesmentioning
confidence: 99%
“…In another study [94], a ligand metal-CS-lecithin complex was prepared as a new strategy to functionalize the surface of PCL nanoparticles. The results showed that the nanoparticulate complex was able to connect recombinant antibody fragments, known as anti-electronegative LDL single-chain fragment variable [scFv anti-LDL(-)].…”
Section: Active and Passive Targeting Of Nanoparticlesmentioning
confidence: 99%